The implementation of a national paediatric oncology protocol for neuroblastoma in South Africa - Jaques van Heerden; Marc Hendricks; Janet Poole; Ané Büchner; Gita Naidu; Jan du Plessis; Barry van Emmenes; Anel van Zyl; Ronelle Uys; Johani Johani; G. P. Hadley; Derek Harrison; et al. (Cancer Causes & Control, 2021)

Have the spawning habitat preferences of anchovy ( Engraulis encrasicolus ) and sardine ( Sardinops sagax ) in the southern Benguela changed in recent years? - Nandipha Mhlongo; Dawit Yemane; Marc Hendricks; Carl D. van der Lingen (Fisheries Oceanography, 2015)
This paper examines whether the ranges of occurrence of anchovy and sardine eggs have changed off the South African coast in recent years, and whether this could be linked to changes in sea surface temperature ( SST ). We used a single parameter quotient analysis with randomization to estimate the preferred and tolerated SST ranges of the spawning habitats of anchovy and sardine in the southern Benguela over the period 1988–2009. Previous studies have reported long‐term change in SST off the South African coast, and our analysis was aimed at determining whether spawning habitat selection by these small pelagic fish tracked such change. The analysis used data on egg occurrence collected concurrently with in situ SST data during annual surveys of pelagic fish biomass conducted along the South African coast. Results show that anchovy typically, but not always, spawn in warmer waters (17.0–23.0°C) than sardine do (16.0–22.0°C), and sardine almost always showed a wider SST tolerance range than did anchovy, over the time‐series. The analysis further suggests evidence of an increase in the surface temperature conditions along the South African coast recently; the spawning patterns of anchovy ( Engraulis encrasicolus ) and sardine ( Sardinops sagax ) appear to track these changes through time. Therefore, the spawning habitat preferences of anchovy and sardine in the southern Benguela have changed in recent years, but this is unlikely to be due to warming alone.